Electrodynamics of Tectonics Processes and Electromagnetic Profiling of the Earth Crust in Antarctica - Pavlovych, V.; Bogdanov, Yu.; Shuman, V.; Vashchenko, V. (Український антарктичний журнал, 2009)
This paper discusses the problems of the natural Earth pulse electromagnetic radiation occurrence and it's usage for the Earth interior exploration. The main attention is paid to radiation of the radiowave diapason (from ~1 kHz to ~1 MHz) which sources is located inside the Earth lithosphere. The nonlinear aspect of mechanic – electromagnetic interaction and electromagnetic wave propagation is discussed. The different models of such a radiation generation and propagation are considered. We have proposed the model of such radiation generation based on the initiation of optical vibrations of complex crystal lattice and therefore associated electromagnetic oscillations that appear due to formation and movement of point, linear (dislocation) and volume (microcracks, pores) defects of crystals. In solid state physics the electromagnetic radiation associated with inherent (optical) lattice vibrations is called polariton radiation. As long as intensity of defect creation is in direct proportion to deformation of the crystal, the intensity of the signal generated will be maximal in maximal deformation zones of the Earth crust. This fact allows the application of this radiation for the Earth crust structure study. Referring to polariton emission, the strained rock is active medium, i.e. the existence of radiation stimulates creation and vanishing of defects leading to radiation amplification. Such mechanism of non-linear amplification of electromagnetic waves together with “transparency windows” existence may explain the observed ultraweak attenuation of such electromagnetic waves in the Earth crust.